Open Access and the Vision of Voices - Stige, Brynjulf (Voices: A World Forum for Music Therapy, 2009)
The Voices vision is 10 years of age. The idea of a free international and electronic journal and forum for music therapy was first discussed at the Ninth World Congress on Music Therapy in Washington, in November 1999. One and a half years later, Voices: A World Forum for Music Therapy was launched at the Fifth European Music Therapy Congress in Naples